2007
DOI: 10.1038/sj.onc.1210325
|View full text |Cite
|
Sign up to set email alerts
|

Multi-step lymphomagenesis deduced from DNA changes in thymic lymphomas and atrophic thymuses at various times after γ-irradiation

Abstract: Whole-body c-irradiation to mice causes thymic atrophy where a population of precancerous cells with mutation can be found. Thus, clonal growth and DNA changes at Bcl11b, Ikaros, Pten, Notch1 and Myc were examined in not only thymic lymphomas but also in atrophic thymuses at various times after irradiation. Clonal expansion was detected from the distinct patterns of rearrangements at the TCRb receptor locus in a fraction of atrophic thymuses at as early as 30 days after irradiation. This expansion may be in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…Bcl11b and Pten, for example, are also altered in early preleukemic cells and in TLs after irradiation, suggesting that they may be key factors of lymphomagenesis. 46 Importantly, Ikaros and Notch1 intersect in the regulation of normal T-cell development. Additionally, leukemogenesis induced by Ikaros deficiency is similar in phenotype to that induced by constitutively active Notch1.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl11b and Pten, for example, are also altered in early preleukemic cells and in TLs after irradiation, suggesting that they may be key factors of lymphomagenesis. 46 Importantly, Ikaros and Notch1 intersect in the regulation of normal T-cell development. Additionally, leukemogenesis induced by Ikaros deficiency is similar in phenotype to that induced by constitutively active Notch1.…”
Section: Discussionmentioning
confidence: 99%
“…To determine D-J rearrangement patterns in the TCRb locus, polymerase chain reaction (PCR) was performed as described. (24,25) Of allelic loss analysis at the Bcl11b locus, D12Mit53 and D12Mit279 markers were used for PCR as described previously. (7) The PCR reaction was processed through 32 cycles of 94°C for 30 s, 55°C for 30 s, and 72°C for 1 min in most cases.…”
Section: Methodsmentioning
confidence: 99%
“…(24) Our previous studies demonstrated that such identical rearrangements were also found in c-ray induced mouse atrophic thymuses, indicating the existence of clonally expanded thymocytes. (24,25) A significant percentage of those thymuses exhibited allelic loss of Bcl11b. These findings raise the question of how and at which stage does the Bcl11b heterozygous genotype contributes to lymphoma development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous chromosomal imbalances have been documented in human lymphomas (Hallermann et al, 2004 Ohi et al (2007) in mice with thymic lymphomas after γ-irradiation In this paper the potential DNA changes in two protooncogenes (N-RAS and c-KIT), and TP53 tumour suppressor gene were analyzed in canine lymphomas.…”
Section: Introductionmentioning
confidence: 99%